An interfacial layer element for finite element analysis of arch dams. (1st December 2016) - Luo, Danni; Hu, Yu; Li, Qingbin
Highlights: ILE is developed to model bimaterial interface or structural joint in FEM analysis. Complex material variation and high deformation gradient are simulated in one ILE. Case study on a real dam justifies large potential of ILEs in engineering practice. Abstract: An interfacial layer element is developed for finite element analysis of engineering structures with interfaces/joints. In order to simulate complex material property variations and high deformation gradients across thin interface/joint regions using coarse meshes, new shape functions and special formulation of stiffness matrix are developed for interfacial layer elements. Two numerical cases are analyzed using the interfacial layer element method in comparison to analytical solutions and the standard element method using fine meshes. The results show that the use of interfacial layer elements substantially reduces the complexity of mesh refinement around interface/joint regions without compromising on the result accuracy. Furthermore, the structural stability of a real arch dam is analyzed by comparing the numerical results obtained by using interfacial layer elements with field monitoring results, and it is found that the interfacial layer element method has large potential in practical engineering applications.